Home visitors and child health in England: advances and challenges - Sarah Cowley (Revista da Escola de Enfermagem da USP, 2011)
There is increasing interest in the early years as a focus for reducing health inequalities as well as one that is important for the children themselves. This paper describes the introduction in England of Sure Start Local Programmes, which included home visiting within a community development approach, and an intensive home visiting programme, the Nurse-Family partnership, for disadvantaged teenage mothers. It reflects on changes and challenges in service provision to mothers and their pre-school children in England, explaining that a long tradition of home visiting was, paradoxically, reduced as attention focused on the newer initiatives. This is now being addressed, with attention to a range of evidence based programmes and a specific focus on heath visitor provision.